2014
DOI: 10.3892/mmr.2014.2021
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA-206 overexpression inhibits cellular proliferation and invasion of estrogen receptor α-positive ovarian cancer cells

Abstract: The expression levels of estrogen receptor (ER α) are closely associated with estrogen-dependent growth, invasion and response to endocrine therapy in ERα-positive ovarian cancer. However, the underlying regulatory mechanisms remain to be fully understood. Previous studies have demonstrated that ERα is a direct target of microRNA (miR)-206. miR-206 has been found to be an important tumor suppressor in several cancer types, including ovarian, gastric and laryngeal cancer. However, the specific role of miR-206 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…miR-206 was found to be significantly downregulated in ERa-positive but not ERa-negative ovarian cancer tissues, compared with normal ovarian epithelium tissue [22]. It was also found that the expression of miR-206 was decreased in ERa-positive ovarian cancer cell lines [22].…”
Section: Discussionmentioning
confidence: 90%
“…miR-206 was found to be significantly downregulated in ERa-positive but not ERa-negative ovarian cancer tissues, compared with normal ovarian epithelium tissue [22]. It was also found that the expression of miR-206 was decreased in ERa-positive ovarian cancer cell lines [22].…”
Section: Discussionmentioning
confidence: 90%
“…Aberrantly altered expression of miRNAs has been found in several cancers including OC, and many miRNAs have been identified as prognostic markers for some cancers [7,8]. In OC, miRNAs act as either oncogenes or tumor suppressor [9,10]. MiR-25 has been found to be increased in OC; however, its detailed role remains unclear [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using highthroughput technology such as miRNA oligonucleotide arrays and quantitative real-time polymerase chain reaction (PCR) for validation have observed the abnormal expression of miR-206 in various human cancer types such as rhabdomyosarcoma (RMS), laryngeal cancer, breast cancer, lung cancer, hepatocellular carcinoma, gastric cancer, endometrial endometrioid carcinoma (EEC) and HeLa cells [14][15][16][17][18][19][20][21]. Especially, Yang et al [19] reported that miR-206 expression was significantly downregulated in gastric cancer tissues when compared with normal adjacent mucosa, and its downregulation might be a potent prognostic marker of this disease; Ren et al [22] revealed that miR-206 could suppress gastric cancer cell growth and metastasis; Zhang et al [23] also confirmed that miR-206 could suppress gastric cancer cell proliferation at least partially through targeting CyclinD2 (CCND2), a crucial regulator in cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%